PEMANFAATAN MEDIA INTERAKTIF EDUCAPLAY DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD - Syifa, Shabrina Fadila; Apriliya, Seni; Alia, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of digital technology has encouraged the integration of interactive learning media to improve the quality of learning in elementary education. However, Indonesian language instruction, particularly poetry (pantun) learning, is still dominated by conventional media that provide limited student engagement, resulting in suboptimal learning outcomes. This study aimed to examine the effectiveness of Educaplay as an interactive learning medium in improving fifth-grade students’ learning outcomes on pantun material compared to PowerPoint. The research employed a quantitative approach using a quasi-experimental design with random sampling. The sample consisted of two fifth-grade classes at SDN 152 Cigagak, involving a total of 50 students assigned to an experimental group and a control group. Learning outcome data were collected through a validated achievement test and analyzed using N-Gain analysis and the Mann-Whitney U test. The results indicated a significant difference in learning outcomes between the experimental and control groups (p = 0.007). The experimental group achieved a higher post-test mean score than the control group, with a moderate N-Gain improvement, while the control group showed a low N-Gain category. These findings confirm that Educaplay, as a game-based and interactive learning medium, is effective in enhancing students’ learning outcomes in pantun learning. The results also imply the need for future studies to focus on strengthening higher-order thinking skills, particularly the C4 (analyzing) indicator.